Sustainable pervious concrete incorporating sorghum husk ash as cement replacement (2019)
The sustainability of Pervious Concrete (PC) can be enhanced by the utilization of waste materials for its construction. Employment of Sorghum Husk Ash (SHA) in partially replacing binder to produce a more sustainable PC was carried out in this research. Preparation of various mixtures of PC was done adopting the same size of aggregate (4.75 – 9.50), the same water/cement ratio (0.4) as well as the same aggregate/cement ration (4:1) and was investigated at 0, 5, 10, 15, 20 and 25 % substitution levels of binder with SHA. Produced PC samples were tested for density, porosity, permeability and compressive strength. The results revealed that density decreased while permeability and porosity raised with rising percentage of SHA. Fresh density was obtained to range from 2000 to 1965 kgm-3 whereas hardened density ranged between 1981 and 1940 kgm-3, 21.5 to 24.5 % values were obtained for porosity while permeability had values of 4.8 to 10.1 mms-1 for 0 - 25 % SHA correspondingly. The compressive strengths of 8.2 Nmm-2 was achieved for 25% SHA and 11.4 Nmm-2 for 0 % at 28 days curing time. The 5% SHA was found to be 13.2 Nmm-2 which is 16 % greater than 0 % SHA PC while that of 10 – 25 % correspondingly reduced by 4.4 - 28.1 %. The research revealed that SHA can practically be utilised to substitute cement with comparable and even make a better mixture than using 100 percent cement in PC fabrication.